Optimization of media composition for the production of bioprotein from pineapple skins by liquid-state bioconversion - Jamal, Parveen; Tompang, Mohd Fahrurrazi; Alam, Md. Zahangir (Asian Network for Scientific Information, 2009)
Two-steps optimization strategy based on statistical experimental design was carried out to enhance bioprotein production by liquid state bioconversion utilizing pineapple skins as substrate. A two-level Plackett-Burman design was employed first where 11 variables were studied for their influence on bioprotein production. Pineapple Skins Soluble (PSS) sugar content, KH2PO4 and NH4H2PO4 were the most significant variables for improving bioprotein production. A three-level Central Composite Design (CCD) was employed for maximizing the bioprotein production. A mathematical model was developed to show the effects of each medium component and their combinatorial interaction on bioprotein production. The optimal medium composition for maximum bioprotein production was PSS content 1.0, KH2PO4 0.1 and NH4H2PO4 0.25. The final experiment was carried out to validate the model, which has shown to produce 514.2 g kg-1 bioprotein on the 5th day of fermentation with a slight increase of 0.02 from the experimental run in CCD. 2009 Asian Network for Scientific Information.